Diplopia and Blurry Vision Following Refractive Eye Surgery: a Comorbidity Case Report - Shushtarian, Seyed Mohammad Masoud; Naghib, Seyed Jalil; Adhami-Moghadam, Farhad; Shojaei, Ahmad (Journal of Ophthalmic and Optometric Sciences, 2020)
Refractive eye surgery is a safe technique as far as visual pathway is concerned. A 39-year patient Complains from diplopia & blurring vision on his second refractive surgery attempt, was referred to visual electrophysiology diagnostic Laboratory of Basir clinic for possible visual pathway disorder. this report explains the visual evoked findings and magnetics resonance imaging of the Patient which indicated a comorbidity of refractive and visual pathway disorders. However, at first glance it considered as side effect of surgery